2014
DOI: 10.1021/pr5005967
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping Polyclonal Kappa and Lambda Light Chain Molecular Mass Distributions in Patient Serum Using Mass Spectrometry

Abstract: We previously described a microLC-ESI-Q-TOF MS method for identifying monoclonal immunoglobulins in serum and then tracking them over time using their accurate molecular mass. Here we demonstrate how the same methodology can be used to identify and characterize polyclonal immunoglobulins in serum. We establish that two molecular mass distributions observed by microLC-ESI-Q-TOF MS are from polyclonal kappa and lambda light chains using a combination of theoretical molecular masses from gene sequence data and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…A strong hint of what testing for M-proteins will be in the near future has come from a team at the Mayo Clinic in the past 2 years [88][89][90]. They have shown that mass spectrometry is an exquisitely sensitive and specific technique that offers great promise to change the entire manner in which M-proteins are characterized and measured [88][89][90].…”
Section: Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…A strong hint of what testing for M-proteins will be in the near future has come from a team at the Mayo Clinic in the past 2 years [88][89][90]. They have shown that mass spectrometry is an exquisitely sensitive and specific technique that offers great promise to change the entire manner in which M-proteins are characterized and measured [88][89][90].…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…They have shown that mass spectrometry is an exquisitely sensitive and specific technique that offers great promise to change the entire manner in which M-proteins are characterized and measured [88][89][90]. Mills et al reported using immunochemical techniques to purify immunoglobulins from other proteins and reduction to separate the heavy and The method to purify and prepare immunoglobulins, followed by microflow liquid chromatography and electrospray ionization with quadropole time of flight mass spectrometry.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…The miRAMM LC mass distribution ( Figure 1B) Patient 1) revealed a markedly skewed polyclonal κ to l light chain ratio (~8) and a polyclonal background seen in other hypergammaglobulinemia patients. 6 Typical IgG κ to l ratios for normal patients is between 1.17-3.61.…”
mentioning
confidence: 99%
“…Methods to overcome this interference in the laboratory have been published but are not yet widely available. MS-based methods have the potential to be utilized (810), and incubation with anti-idiotypic antibodies against the therapeutic MAb changes its electrophoretic migration, allowing it to be discriminated from the original endogenous clone when they comigrate by SPEP and IFE (11). Immunoassays may also be impacted by the presence of therapies such as DARA, which causes panreactivity in antibody screenings in transfusion medicine, as recently reported by blood banking services (12).…”
Section: Why Measure Therapeutic Mabs In the Clinical Laboratorymentioning
confidence: 99%